The Alexander Decadrachms of Babylon - Taylor, Lloyd W. H. (KOINON: The International Journal of Classical Numismatic Studies, 2021)
This essay examines the impact of recent examples in commerce on our understanding of the Babylonian decadrachms bearing the image of the head Herakles (obverse) and Zeus enthroned (reverse) struck under Alexander the Great in 325-324 BC. The Babylonian decadrachms of Alexander the Great were first documented in the nineteenth century with two examples from a hoard in commerce; the Babylon 1849 Hoard (IGCH 1749).